Removal of Cr(VI) from Wastewater Using a Natural Nanoporous Adsorbent: Experimental, Kinetic and Optimization Studies - Utkarsh Maheshwari; Suresh Gupta (Adsorption Science & Technology)
In the present work, a nanoporous adsorbent prepared from low-cost neem bark is used for the removal of chromium (VI) ions from wastewater. The adsorbent is characterized by scanning electron microscopy, energy-dispersive spectroscopy, BET surface area, infrared analysis and X-ray diffraction analysis. The effect of various parameters such as adsorbent dosage, pH, initial concentration and contact time for the removal of chromium (VI) ions has been studied. The data obtained have been tested with various isotherm and kinetic models. Langmuir model is found to be the best suited isotherm model giving maximum adsorption capacity as 26.95 mg g −1 for the removal of chromium (VI) ions. Effluent from a plating industry was also used to evaluate the performance of the developed adsorbent. Weber and Morris and Boyd models show that both intra-particle and film diffusion are the controlling mechanism for adsorption of chromium (VI) ions on the developed adsorbent. The mathematical model is developed to optimize the adsorption capacity (q) in terms of the influencing parameters with the help of differential evolution (DE) technique.